Aristotle as an Idealist - Pajares, Glenn G. (JPAIR Multidisciplinary Research, 2012)
The ancient Greek philosopher Aristotle is widely known as a realist in believing that the real exists in the sensible world and can be known through sense of perception or observation. But, there are others who would claim that he is a moderate realist in believing that the essences are one with physical objects but are known universally and immaterially. Contrary to these popular beliefs, this paper discussed that Aristotle is neither a realist nor a moderate realist but an idealist. The study utilized descriptive critical analysis as its method. The author explained the basic principles and teachings of Aristotle on metaphysics, epistemology and dwelt on these basic principles and teachings as bases of criticism. This article presented Aristotle's belief that the true essences of things which he referred to as forms, essences or substance are metaphysical or universal which is beyond the physical and therefore beyond the grasp of sensation and observation. In other words, reality for him is only logical or mental in nature for it is not tangible. This also explained that Aristotle's theory of knowledge (epistemology) which employed the senses to grasp the essences of things is not possible.